Cytrellis: A Novel Microcoring Technology for Scarless Skin Removal: Summary of Three Prospective Clinical Trials - Jason N. Pozner, MD (Wolters Kluwer, 2021)
Background:. We introduce an innovative and novel technology that achieves scarless skin removal without the use of thermal energy. Microcoring technology (MCT) uses a modified, hollow hypodermic needle to remove skin safely and without a scar. This method is advantageous compared to other fractional devices, given that it has the same benefits as energy-based devices (removal of skin cores without a scar), with the added value of immediate closure along the relaxed skin tension lines, with significantly less thermal energy. Methods:. Three prospective clinical safety trials analyzing MCT treatment on abdominal and facial skin (short- and long-term) are described. Results:. MCT treatment of human skin resulted in scarless skin removal that was well tolerated by patients. Healing occurred rapidly, with limited side effects. Skin area reduction (skin tightening) and increase in skin thickness were observed long term. Conclusions:. MCT treatment of human skin is safe and well tolerated. Although further studies on efficacy are required to evaluate the full potential of MCT in skin rejuvenation, early findings such as skin tightening and increase in skin thickness are encouraging.